Urgency of the Role of Society in Protection Conservation Area (Faculty of Law Universitas Negeri Semarang, 2022)
Indonesia has at least 54 National Parks (Taman Nasional) and 123 Nature Tourism Parks (Taman Wisata Alam) with an area of 16 million ha. In addition to national parks and Nature Tourism Parks, the potential of natural tourism in conservation areas in Indonesia is also located 28 units Forest Park, Buru Park 11 units, Nature Reserve 219 units, Wildlife Sanctuary 72 units, and Nature Reserve Area /Nature Conservation Area as much as 56 units. However, there is still unlicensed forest control, illegal logging, falsification of documents, smuggling of rare animals or plants, forest fires and etc. This can be a threat to the presence of rare animals and plants in conservation areas. In addition, with so many conservation areas, it requires intensive security and supervision. Communities adjacent to conservation areas, can be more sensitive and responsive to problems that occur. The community will play an active role ranging from planning, implementation, to monitoring and evaluation of protection development. So it needs to be examined, how urgency the role of the community in the protection of conservation areas. The research method used is juridical research with legal approach and concept.